HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR MATA PELAJARAN ILMU GIZI SISWA KELAS X JASA BOGA SMK NEGERI 9 PADANG - Dwi, Elfrimo; Elida, Elida; Yulastri, Asmar (Journal of Home Economics and Tourism, 2015)
This research was purpose to, 1) Describe the students motivation of Nutrition subject in class X catering services SMKN 9 Padang, 2) Describe the results of the student learned of Nutrition subject in class X catering service SMKN 9 Padang, 3) Reveal the relation between motivation with the results of student learning on Nutrition Subject class X Catering services SMKN 9 Padang. The genre of the research was is correlation quantitative. This research was conducted in SMK Negeri 9 Padang in May 2015. The population of the research is all of the students of class X catering service SMKN 9 Padang. The sample of this research is about 30 person by using random sampling techniques. The results of this research showing that the learning motivation has a high number and standing on pass enough category. The relation between motivations with the result of learning of nutrient science students has positive relation and significant with the value rhitung > rtabel (0,400 > 0,361) with interpretation correlation coefficient was average.Keyword : Motivation, Student Learning, Nutrition